A study on the relationship between motivation and language learning achievement among tertiary students - Binalet, Cedra B. (Animo Repository, 2014)
Motivation has been regarded as the driving force to learn a language. Aside from the notion that motivation is an influential facet to language learning, motivation can also be regarded as varied among learners’ gender, socioeconomic status and perception towards the language learning task. The success or failure of language learners to use and further effectively acquire a language is said to be relative to the motivation they put in learning or studying a language. The present study makes use of an instrument based on the initial questionnaire made by Noels, et al., 2000 to measure the motivational levels of the students. To prove the reported motivation of the respondents, they were also tasked to judge the grammaticality of sentences in the second instrument. After the gathering of data and the subsequent analyses, it was found that motivation may not be greatly related to language learning success of the respondents. © Australian International Academic Centre, Australia.